Der Gregärparasitismus von Trichogramma (Hymenoptera: Trichogrammatidae). - Schieferdecker, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The quantifiable parameters of the host-parasite-relations concerning the gregarious parasitism of Trichogramma show a very complicated structure, being interdependent or modifying the manifestations of certain causal relations. With the increasing number of available host eggs the density of parasites decreases. On the first days twice as many parasite eggs are deposited as in those inveded later. The parasites from eggs with a high density of deposition emerge up to four days earlier. The time of oviposition depends on the size of the host egg. T. embryophagum in bigger host eggs has an endogenous diapause that does not depend on abiotic factors but on the density of parasites. Different Trichogramma species can grow side by side in the same host egg without any noticeable additional interspecific competition.